Revitalisasi Pendidikan Pemikiran Islam (Studi Kasus Pemikiran Al-Attas dan ISTAC Malaysia) - Anton Ismunanto (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
One of impressive definition from education is the art of humandevelopment. Humans are creatures that has many aspects, ormultidimensional. One of human’s potentials that can be developedis their opinion. Because truthfully, a human’s opinion impact on hisbeliefs, attitudes and actions. With right education worldview, aMuslim will be able to reproduce the ideas underlying the realizationof ‘the perfect human’ or ‘universal human’ as a destination for Highlevel of Islamic education. This Papers discuss the profile of SyedMuhammad Naquib al-Attas and the realization of his ideas aboutan Islamic university in the International Institute of Islamic Thoughtand Civilization (ISTAC), it found the superior intellectual of thefounder as well as the mastery in some fields of science, it impactson the quality of educational institutions which he founded. Whenthe idea of al-Attas is adopted to institution, the quality of collegephilosophy is very noticeable, such as in terms of curricula, courses,educator, architectural design both interior and exterior, also to thelibrary and publishing quality.